Revisiting cheerful Jane and miserable John: The impact of income, good health, social contacts and education declines with increasing subjective well-being - Martin Binder (Philipps-University Marburg, Department of Geography, 2015)
This short note seeks to replicate the quantile regression analysis in Binder and Coad (2011), but taking into account individual-specific fixed effects (using the BHPS data set). It finds declining effects of the four main variables of interest (health, social life, income, education) over the quantiles of the subjective well-being distribution, with attenuated effect sizes for the fixed-effects model. Equivalized log income has a negative impact on subjective well-being throughout the distribution. Apart from a number of robustness checks, existing research is extended by looking into the quantile effects of the above variables on a set of domain satisfactions.
Keywords: I12; I31; R15; 330; subjective well-being; quantile regressions; heterogeneity; BHPS; life satisfaction